Self-perceived ability to cope with stress without smoking predicts successful smoking cessation 12 months later in a quitline setting: a randomized trial - Eva Nohlert; John Öhrvik; Ásgeir R Helgason (Tobacco Induced Diseases, 2018)
Background Telephone-based smoking cessation services ('quitlines') are both effective and cost-effective. Knowledge of modifiable baseline factors in real-life settings with heterogeneous participants is essential for the development and improvement of treatment protocols to assist in telephone-based smoking cessation. The aim was to assess self-efficacy as a predictor for abstinence at the 12-month follow-up at the Swedish National Tobacco Quitline (SNTQ).